Immunotherapy in Breast Cancer and the Potential Role of Liquid Biopsy - Magbanua, Mark Jesus M.; Gumusay, Ozge; Kurzrock, Razelle; van ‘t Veer, Laura J.; Rugo, Hope S. (Frontiers in Oncology, 2022)
Liquid biopsy biomarkers, such as circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA), are noninvasive diagnostics that could complement predictive and prognostic tools currently used in the clinic. Recent trials of immunotherapy have shown promise in improving outcomes in a subset of breast cancer patients. Biomarkers could improve the efficacy of immune checkpoint inhibitors by identifying patients whose cancers are more likely to respond to immunotherapy. In this review, we discuss the current applications of liquid biopsy and emerging technologies for evaluation of immunotherapy response and outcomes in breast cancer. We also provide an overview of the status of immunotherapy in breast cancer.